Effects of Low-Load Blood-Flow Restricted Resistance Training on Functional Capacity and Patient-Reported Outcome in a Young Male Suffering From Reactive Arthritis - Jørgensen, Stian Langgård; Mechlenburg, Inger (Frontiers in Sports and Active Living, 2021)
Introduction: Reactive arthritis (ReA) is a chronic inflammatory disease usually caused by a preceding gastrointestinal or genitourinary bacterial infection. ReA usually occurs in the lower limbs causing joint pain and joint swelling. Physiotherapy-led exercise is recommended to prevent muscle atrophy. The purpose of this case report is to describe the outcome after 12 weeks of low-load blood flow restricted resistance training (BFR-RT) as a rehabilitation method for a young male suffering from ReA. Methods and materials: A 17-year-old male suffered from ReA in the both knee joints and the left hip joint. 36 months after the incident, he suffered from another ReA incident in his right knee. Non-steroid anti-inflammatory drugs and a new arthrocentesis added with corticosteroid injection was unsuccessful in treating the ReA. The patient performed 12 weeks of BFR-RT on the right lower limb with a low amount of supervision after the first week of training. Assessment of unilateral 30-sec chair stand test (u30-sec CST), low-thigh circumference above apex patella, The Knee Injury and Osteoarthritis Outcome Score (KOOS), The Forgotten Knee Joint Score (FJS), and Numeric Ranking Scale for pain (NRS) was performed at baseline and after 3,6,9, and 12 weeks of BFR-RT. Results: The patient completed all planned exercise sessions. u30-sec CST improved with 7 repetitions (reps) on the right limb and 5 reps on the left leg. Low-thigh circumference decreased 1.1 cm on the right leg and 1.0 on the left leg. KOOS symptoms, ADL, quality of life and FJS demonstrated a clinically relevant change on 10, 14 and 23 points. Conclusion: The present case study indicates that even with low amounts of supervision BFR-RT could increase functional performance, reduce knee joint swelling and improve key patient-reported outcome.